Structural brain abnormalities in adolescents with autism spectrum disorder and patients with attention deficit/hyperactivity disorder - Brieber, Sarah; Neufang, Susanne; Bruning, Nicole; Kamp-Becker, Inge; Remschmidt, Helmut; Herpertz-Dahlmann, Beate; Fink, Gereon R.; Konrad, Kerstin (Journal of child psychology and psychiatry, 2007)
Background:  Although autism spectrum disorder (ASD) and attention deficit/hyperactivity disorder (ADHD) are two distinct neurodevelopmental diseases, they share behavioural, neuropsychological and neurobiological characteristics. For the identification of endophenotypes across diagnostic categories, further investigations of phenotypic overlap between ADHD and autism at the behavioural, neurocognitive, and brain levels are needed. Methods:  We examined regional grey matter differences and similarities in children and adolescents with ASD and ADHD in comparison to healthy controls using structural magnetic resonance imaging (MRI) and voxel‐based morphometry. Results:  With regard to clinical criteria, the clinical groups did not differ with respect to ADHD symptoms; however, only patients with ASD showed deficits in social communication and interaction, according to parental rating. Structural abnormalities across both clinical groups compared to controls became evident as grey matter reductions in the left medial temporal lobe and as higher grey matter volumes in the left inferior parietal cortex. In addition, autism‐specific brain abnormalities were found as increased grey matter volume in the right supramarginal gyrus. Conclusions:  While the shared structural deviations in the medial temporal lobe might be attributed to an unspecific delay in brain development and might be associated with memory deficits, the structural abnormalities in the inferior parietal lobe may correspond to attentional deficits observed in both ASD and ADHD. By contrast, the autism‐specific grey matter abnormalities near the right temporo‐parietal junction may be associated with impaired ‘theory of mind’ abilities. These findings shed some light on both similarities and differences in the neurocognitive profiles of ADHD and ASD patients.